ANALISIS SUHU PERMUKAAN LAUT SAWU TAHUN 2021 MENGGUNAKAN CITRA SENTINEL-3 - Handoko, Eko Yuli; Syariz, Muhammad Aldila; Wicaksono, Krisna Wahyu (J SIG (Jurnal Sains Informasi Geografi), 2023)
The eastern part of Indonesian Seas has a very unique characteristic as it is traversed by the Indonesian Through Flow (ITF). The ITF is a movement of water masses from the Pacific Ocean to the Indian Ocean, driven by the pressure differences between these two oceans. The movement of water masses and currents, along with the existence of monsoon winds that blow across the region throughout the year, impact the Sea Surface Temperature (SST) in Indonesia. The SST can be derived from satellite imagery such as MODIS and SeaWIFs images. This study utilized Sentinel-3 Sea and Land Surface Temperature data, with better spatial and temporal resolution than the two aforementioned images, to process the Sea Surface Temperature values. The research also investigated sea surface temperature values correlation with the movement and speed of winds occurring in Indonesia. The research results presented the monthly time-series distribution of sea surface temperature values in the Savu Sea for the year 2021. The analysis revealed that the lowest sea surface temperature values occurred in July, while the highest were recorded in December. The sea surface temperature values per month demonstrated an increase during the westerly monsoon from October to April, which corresponds to the rainy season in Indonesia. Conversely, during the easterly monsoon, the sea surface temperature values tended to be lower, resulting in the dry season due to decreased ocean evaporation. Furthermore, the study found a negative correlation between sea surface temperature values and wind speed, with a strong correlation coefficient of -0.5709.